2020
DOI: 10.3390/molecules25092084
|View full text |Cite
|
Sign up to set email alerts
|

Tricin Isolated from Enzyme-Treated Zizania latifolia Extract Inhibits IgE-Mediated Allergic Reactions in RBL-2H3 Cells by Targeting the Lyn/Syk Pathway

Abstract: Tricin, a flavone present in rice bran, is confirmed as the major efficacious compound present in the enzyme-treated Zizania latifolia extract (ETZL), which protects against UVB-induced skin-aging. However, the suppressive mechanism of tricin on allergic responses remains unknown. The present study, therefore, aimed to determine the mechanisms of tricin and ETZL on mast cell degranulation in IgE-activated rat basophilic leukemia cell line (RBL-2H3) cells. We investigated the regulatory effects of tricin and ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Tricetin is a potential anti-inflammatory and anticancer agent ( Chang et al, 2017 ; Chung et al, 2017 ). Tricin showed anti-allergic ( Lee et al, 2020 ) and anti-cancer ( Li et al, 2021 ) activities. In this study, naringin was mainly found in the leaves collected at high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Tricetin is a potential anti-inflammatory and anticancer agent ( Chang et al, 2017 ; Chung et al, 2017 ). Tricin showed anti-allergic ( Lee et al, 2020 ) and anti-cancer ( Li et al, 2021 ) activities. In this study, naringin was mainly found in the leaves collected at high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exposure of IgE‐activated RBL‐2H3 MCs to tricin, a flavone in rice bran, suppressed production of TNF‐α, IL‐4, leukotrienes (LT) B 4 , LTC 4 , and prostaglandin E 2 by significantly decreasing the phosphorylation of the tyrosine‐protein kinase (Lyn) and spleen tyrosine kinase (Syk) 137 . This suggested that the Lyn/Syk axis as a new potential target for prevention of IgE‐mediated allergic reactions.…”
Section: Therapeutic Potentials Targeting Circadian Mc‐mediated Histamentioning
confidence: 99%
“…According to the reports of Mohanlal et al [16], Kwon and Kim [17] and Quan et al [18], the tricin content of Oryza sativa calculated 48.6 mg/kg, 32.9 mg/kg, and 0.55 mg/kg, respectively. Tricin suppressed the arachidonic acid signal, mitogen-activated protein kinase (MAPK), and FcεRI signal of the RBL-2H3 cells and showed anti-allergic effects by suppressing the release of LTB4, LTC4, and PGE2 [19]. Indeed, Jiang et al [20] revealed that tricin has effectively the biological properties by functional groups such as phenolic hydroxyl groups, carbonyl groups, methoxyl groups.…”
Section: Introductionmentioning
confidence: 99%